NATIONAL SECURITY TRANSFORMATION: RESILIENCE WITHIN NATIONAL SECURITY STRATEGIES OF GREAT POWERS IN RESPONSE TO GLOBAL THREATS - Keković, Zoran; Dinić, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Altered nature of security risks and threats created within globalization process new security environment, forcing creators of national security strategies to anticipate the sources of threats and to define appropriate mechanisms for response to different forms of security threats addressed to states and its citizens. The concept of resilience is taken from technical sciences and implemented in the security strategies of  great powers as a potential solution for strengthening capacity and system preparedness for responding to threats as well as the rapid recovery, regardless of intelligence analysis and assessment of relevant institutions.